2004
DOI: 10.1038/oby.2004.134
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diet and Time of the Day on Serum and CSF Leptin Levels in Osborne‐Mendel and S5B/Pl Rats

Abstract: ISHIHARA, YURI, CHRISTY L. WHITE, HARUAKI KAGEYAMA, ASAKO KAGEYAMA, DAVID A. YORK, AND GEORGE A. BRAY. Effects of diet and time of the day on serum and CSF leptin levels in Osborne-Mendel and S5B/Pl Rats. Obes Res. 2004;12:1067-1076. Objective: To characterize the effects of dietary fat on the diurnal variation in serum and cerebrospinal fluid (CSF) leptin levels in Osborne-Mendel (OM) and S5B/Pl rats and quantitate the dose response to lower doses of leptin administered into the third cerebral ventricle. Rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 49 publications
0
11
1
Order By: Relevance
“…By contrast, Lin et al (37) reported that Osbourne Mendel rats were resistant to peripheral injections of leptin after only 5 days on a 56% kcal fat diet (37). The reason for the rapid onset of resistance in this study may be associated with the obesity-prone Osbourne Mendel rats, which are relatively leptin resistant even on a LFD (26). The cause of leptin resistance in HFD-fed rats and mice has been associated with a downregulation of leptin receptors (39) and increased expression of suppressor of cytokine signaling 3 (15,62) and protein tyrosine phosphatase 1B (69), both of which inhibit leptin receptor signaling.…”
Section: Discussioncontrasting
confidence: 51%
“…By contrast, Lin et al (37) reported that Osbourne Mendel rats were resistant to peripheral injections of leptin after only 5 days on a 56% kcal fat diet (37). The reason for the rapid onset of resistance in this study may be associated with the obesity-prone Osbourne Mendel rats, which are relatively leptin resistant even on a LFD (26). The cause of leptin resistance in HFD-fed rats and mice has been associated with a downregulation of leptin receptors (39) and increased expression of suppressor of cytokine signaling 3 (15,62) and protein tyrosine phosphatase 1B (69), both of which inhibit leptin receptor signaling.…”
Section: Discussioncontrasting
confidence: 51%
“…Previous reports have suggested that the obesity-prone OM and obesity-resistant S5B rats differ neurochemically, behaviorally, and physiologically in their response to consumption of dietary fat [1, 3, 4, 8, 2939]. Several studies have impacted the focus of the current experiments and led to the investigation of differences in the GI tract of these rats.…”
Section: Discussionmentioning
confidence: 96%
“…For example, in rats susceptible to obesity (Osborne-Mendel rats) the amplitude of rhythm of leptin and insulin was about 50% that in rats relatively resistant to obesity [45]. Other 24 h rhythms are affected by high-fat diet in animals.…”
Section: Discussionmentioning
confidence: 98%